VISUALISASI MODEL 3D UNTUK SISTEM INFORMASI PENGGUNAAN GEDUNG (Studi Kasus : Gedung Teknik Geomatika, UPMB dan UPMS Kampus ITS) - Cahyono , Agung Budi; Rafitricia, Anindya N (Departemen Teknik Geomatika ITS, 2017)
Buildings serve several needs of society – primarily as shelter from weather, security, living space, privacy, to store belongings, and to comfortably live and work, including using it for classes in ITS Surabaya. The development of information provision can be done by improving the visual aspect and the accuracy of the information as well. It is time to begin improving the 3D visualization which accommodates the space aspect. 3 dimensional approach deemed appropriate for the provision of management information related to the building utilization. In this case, it is about classrooms.There are several phases in 3D modeling integrated with the non-spatial database to make a system that provide the information about building utilization. Those are the data collection process, 3D model visualization, creating a database for textual data, relating spatial data and non-spatial data and creating the interface which will provide the whole information using Visual Studio. 3D modeling data obtained from the building blueprint construction by PIMPITS and the class schedules obtained from UPMB ITS. The final outcome from the visualization of the 3D models contains 3 buildings with a total of 138 rooms with 72 rooms in Geomatics Engineering, 36 rooms in UPMB and 30 rooms in UPMS. Yet the 3D model had connected with the non-spatial database which contains 7 tables and queries that provides the information of the objects.